Women’s Roles in Education and Social Welfare Development: Insights from a Qualitative Study - Hamid, Shazia; Bushra Sumaya (Women, Education, and Social Welfare, 2025)
This study explores the pivotal roles of educated women in advancing family and community welfare within the Indonesian context, where education intersects with cultural, moral, and socio-economic dimensions of empowerment. Grounded in the premise that education enhances women’s agency and social participation, the research employed a qualitative approach to capture the lived experiences of women in urban and peri urban areas of Bandar Lampung. Data were collected through semi structured interviews and non-participant observation involving purposively selected participants who had completed at least secondary or tertiary education and were engaged in welfare-related activities. Thematic analysis revealed four major findings: first, education functions as a catalyst that strengthens women’s decision-making, financial literacy, and community engagement; second, moral and ethical awareness derived from education motivates women to assume leadership roles in promoting collective welfare; third, women’s ability to balance domestic responsibilities and social involvement reflects adaptive strategies rooted in educational empowerment; and fourth, digital literacy emerges as a critical enabler for welfare innovation and socio-economic resilience. These findings align with and extend existing literature on women’s education and welfare, offering new insights into the integration of cognitive, moral, and social empowerment as a unified framework for sustainable development. The study concludes that education transforms women into agents of social transformation whose influence transcends the household, shaping intergenerational well-being and community sustainability. The implications of this research emphasize the need for gender-responsive educational policies, curriculum integration of leadership and digital literacy, and inclusive welfare programs that acknowledge women’s informal and moral contributions as vital components of national and community development.